Implementasi Predictive Maintenance Menggunakan Metode Infrared Thermography Pada Peralatan Listrik di PT Pertamina Hulu Mahakam - Aji Sayuthi Ramadhan; Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Predictive Maintenance is a maintenance activity that focuses on monitoring equipment conditions in real-time and analyzing data to predict potential failures before they occur, allowing repairs to be made in a timely manner before major damage occurs. One of the methods used in predictive maintenance is